2012
DOI: 10.4025/actascianimsci.v34i2.12469
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between feeding rate and area for periphyton in culture of Nile tilapia juveniles - doi: 10.4025/actascianimsci.v34i2.12469

Abstract: The objective of the present work was to determine the effects of the interaction between feeding rate and area for periphyton in rearing aquaria for Nile tilapia. Twenty 25 L polyethylene outdoor aquaria were used to hold experimental fish. Three tilapia fingerlings (2.56 ± 0.14 g) were stocked in each aquarium for five weeks (12 fish m-2). There were two different feeding rates (full and full minus 30%) and two submerged areas for periphyton development (59.4% and 96.5% of the aquarium surface area; n = 5). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…For PVC pipes based treatments, total fish biomass was 1.18, 3.64 and 0.75 times higher than control treatment for L. rohita, C. mrigala and G. catla respectively. The results are in agreement with those of Azim et al (2004), Cavalcante et al (2011) and Reboucas et al (2012) who have also reported higher fish production in periphyton based culture systems due to improved water quality. A comparison of the two substrates for periphyton growth showed that use of bamboo poles resulted in higher survival rate and fish production of L. rohita in comparison to PVC pipes.…”
Section: Resultssupporting
confidence: 92%
“…For PVC pipes based treatments, total fish biomass was 1.18, 3.64 and 0.75 times higher than control treatment for L. rohita, C. mrigala and G. catla respectively. The results are in agreement with those of Azim et al (2004), Cavalcante et al (2011) and Reboucas et al (2012) who have also reported higher fish production in periphyton based culture systems due to improved water quality. A comparison of the two substrates for periphyton growth showed that use of bamboo poles resulted in higher survival rate and fish production of L. rohita in comparison to PVC pipes.…”
Section: Resultssupporting
confidence: 92%
“…While IMTA-Ulva lactuca and Gracilaria spp. have been indicated as nutritious feed in culture of abalone [40], sea urchins [41] and fish [42], the potential of IMTA-periphyton is to some extent unknown. To overcome this gap, a series of nutrition trials were performed at NCM.…”
Section: Periphyton For Feeding Of Cultured Marine Fishmentioning
confidence: 99%